Ethnobotany and conservation applications in the Noken making by the Sougb Tribe of West Papua, Indonesia - YORIS SAIBA; ANTONI UNGIRWALU; AGUSTINUS MURDJOKO; FRANCIS Q. BREARLEY; MARIANA H. PEDAY; RINA NELLY YOWEI; CHRISTIAN SOLEMAN IMBURI; YUBELINCE Y. RUNTUBOI; DONY ARISTONE DJITMAU; SITI HALIMATUS SA'DIYAH (Society for Indonesian Biodiversity, 2023)
Abstract. Saiba Y, Ungirwalu A, Murdjoko A, Brearley FQ, Peday MH, Yowei RN, Imburi CS, Runtuboi YY, Djitmau DA, Sa'diyah SH. 2023. Ethnobotany and conservation applications in the Noken making by the Sougb Tribe of West Papua, Indonesia. Biodiversitas 24: 4577-4583. Documenting local ecological knowledge is critical for understanding complex ecological-cultural interactions to protect indigenous community entities. Woven baskets known as Noken have been part of Papuan indigenous culture for centuries, yet ethnobotanical aspects of Noken making remain poorly understood. Hence, this study describes Noken-making from an ethnobotanical perspective. We acquired ethnoecological knowledge by interviewing respondents who were actively involved in the production of Noken. The results revealed that the Sougb Tribe (from South Manokwari District, West Papua, Indonesia) utilized pineapple as a primary material for weaving and other natural materials as dyes, with this process undertaken mainly by women. We also document the Sougb Tribe's adaptation and continuous interaction with their dynamic environment that has evolved during Noken's making. Moreover, the recommendation to conserve Noken preserves biocultural diversity and habitats for key plant species. Since Noken has played an essential part in shaping the Sougb Tribe's cultural identity, conserving the use of Noken will aid in preserving the habitats of plants used as materials for Noken. In the future, the provincial government should assist habitat biocultural conservation by granting tribes customary forest status to facilitate plant habitat protection in line with the sustainable development agenda of West Papua Province.